Strategi Partai NasDem dalam Meningkatkan Partisipasi Politik Non-Formal Anak Muda Melalui Program NasDem Muda dan Remaja Bernegara (RBN) - Wicaksono, Ibrahim Reyhan; Aji, Muhammad Prakoso (Jayapangus Press, 2025)
Youth political participation in Indonesia is characterized by strong demographic weight but weak involvement in party organizations, creating a gap between electoral participation and organizational engagement. This study analyzes the NasDem Party’s strategy to promote non-formal political participation among young people through the NasDem Muda and Remaja Bernegara (RBN) programs. Using a descriptive qualitative approach that combines literature review, documentation, interviews, and social media observation, the research applies Herbert McClosky’s theory of political participation and Harold D. Lasswell’s model of political communication. The findings show that NasDem Muda functions as an accessible digital entry point, while RBN provides more intensive experiential learning through training and simulations. Together, these programs increase youth political literacy, shift participants from apathetic or spectator positions toward more active non-formal engagement, and open informal recruitment channels without requiring formal party membership. The novelty of this study lies in its comparative analysis of two party-led models of non-formal political education based on experiential learning within a single political organization. The study contributes theoretically by linking participation and communication frameworks with the practice of youth-oriented party education, and offers practical guidance for parties in designing participatory, youth-oriented political education programs.